Al-Ghazali’s Concept of Happiness in The Alchemy of Happiness - Soleh, Achmad Khudori (Journal of Islamic Thought and Civilization, 2022)
Al-Ghazali’s book entitled The Alchemy of Happiness describes happiness. It often becomes a reference of behavior of mysticism and psychology, especially Islamic psychology. However, there are no studies that specifically examine this book. This study analyzes al-Ghazali’s concept of happiness in The Alchemy of Happiness. The research data sources consist of literature having The Alchemy of Happiness as their main references. The researcher uses the content analysis method to analyze the data. The research results show that (1) Al-Ghazali’s concept of happiness refers to the Qur’an, Hadīths, Islamic philosophy, Sufism teachings, and al-Farabi’s leadership concept. (2) Al-Ghazali’s principle of happiness is twofold: that happiness must be pursued and tiered. Al-Ghazali’s concept of happiness consists of four aspects: appetence, reason, heart, and love for Allah. (3) Furthermore, the method of achieving happiness has three stages, (1) recognizing the nature and character of the self, (2) placing the heart as the leader of the self, and (3) contemplation of God. Al-Ghazali’s concept of happiness has several advantages, namely use many Quarnic references; does not eliminate the potential for lust; and does not teach fatalism. In fact, he motivates people to pursue their happiness. Keywords: Al-Ghazali, Alchemy of Happiness, Concept of happiness, aspects of happiness, Methods of achieving happiness